ESCAPISM AS A MANIFESTATION OF UNFULFILLED DREAMS IN CARL SANDBURG’S POEMS DREAM IN THE DUSK AND WAITING - Dianti, Pramu (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2013)
This final project is about Escapism. The objectives of this study are to analyze dreams that are not fulfilled in the poems, to analyze how the poem reveals the poet’s escapism through poetic devices such as imagery and figures of speech and to describe how escapism as a manifestation of unfulfilled dreams in the poems viewed from Freud’s theory. The psychological approach used in analysing these poems is Freud’s psychoanalysis. The researcher analyzes the case of escapism as a manifestation of unfulfilled dreams in the poems. Qualitative method is used in this study, while library and other references are used here to get data. The data are focused on words, stanzas, imagery and figures of speech in the poems. Then the researcher starts to analyze and finally report the answer of statements of the problem. There were some results discovered in this study. First, in Dream in the Dusk, the poet dreams to be a rich person and in Waiting, the poet dreams of his home. Second, the poems reveal the poet’s escapism as a manifestation of unfulfilled dreams through poetic devices such as imagery and figures of speech. It has the poet’s message and figures of speech which show escapism in the poems. At last, escapism as a manifestation of unfulfilled dreams viewed from Freud’s psychoanalysis shows that escapism found in this poem is fantasy of the poet that makes him feel better, and it can also make him forget the distressed feelings caused by reality. The final conclusion of the study is that the poet cannot reach his dreams. It makes him sad and despair, so, he escapes from his sadness by fantasizing.